Clinical profile and bacteriological eitiology in cases of acute exacerbation of COPD in a tertiary care: a tertiary care study - Neelamma, K. A. Sahana; E., Dinesh Ragav (International Journal of Advances in Medicine, 2021)
Background: Acute exacerbation a prominent feature of COPD, is a major entity altering the course of the disease. These exacerbations are by complex interactions between host, bacteria, viruses and environment. Many studies done earlier indicate bacteria being the major cause of these exacerbations. This study is hence done to determine the bacteriological profile, haematological profile severity and grade clinical signs and symptoms based of ‘Gold’ criteria. Methods: A cross sectional descriptive study, done on a total of 80 cases for a period of 18 months on patients admitted to Sathya Sai medical college with acute exacerbations of chronic obstructive pulmonary disease. Cases of acute exacerbation of COPD satisfying the eligibility criteria were included in the study. Clinical and microbiological parameters were noted with special preference to sputum culture and spirometry. Results: Bacteria was not present in 46 (57.5%) of the study population. Klebsiella pneumoniae was present in 12 cases (15.0%), pseudomonas aeruginosa in 6 (7.5%), staphylococcus aureus in 6 (7.5%), streptococcus pneumoniae in 5 (6.2%) and actinobacter in 5 (6.2%). 34 cases were sensitive to antibiotics (52.5%). Majority being sensitive to ceftriaxone, piperacillin and levofloxacillin. 43 cases belonged to ‘Gold’ criteria on spirometry. Hyper inflated lung, tubular heart was present in 39 (48.8%) cases. With normal chest X-ray findings in the rest. Conclusions: Bacteria causing exacerbations is different in India as compared to other studies from different countries. Klebsiella pneumonia being most common organism followed by Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus pneumoniae and actinobacter. AECOPD patients with bacteria showed sensitivity to ceftriaxone, piperacillin and levofloxacillin. Hence, these etiology with sensitivity pattern should be kept in mind for starting a patient on empirical antibiotic therapy.